Trust Measurement in an Enterprise. A Conceptual Approach - Rudzewicz, Adam (Olsztyn Economic Journal, 2018)
This paper presents the meaning of trust in the operation of enterprises and presents three original research tools to measure three areas of trust (internal, inter-organizational and consumer), which the author uses to form a complete construction of trust at the enterprise level. Measurement assumptions are based on literature studies. The proposed division trust into three areas is justified by the fact that the process of trust development involves various entities and different factors determine specific areas of trust. The author tried to organize and demonstrate the most relevant contemporary dimensions of trust, including employee care, concern for stakeholders, competence, reliability, honesty and openness. The diagnosed dimensions of trust at the general level were then developed into an operational and measurement form, which should best describe the proposed areas of trust. In the process of measurement of trust within the classification proposed was assessed and appropriate research medel were developed. Examples of empirical allowed to determine the usefulness of the proposed measurement tools. The research tools used for this purpose are comprehensible and suitable for management practice, they do not oversimplify reality. The concept of systemic trust analysis satisfies the reliability criterion and it can be hoped that it reflects, to the highest possible degree, the reality in which enterprises operate.